A critical investigation of diffuse double layer changes in clay-electrolyte systems at high temperatures - AL-Bazali, Talal (Journal of geophysics and engineering, 2022)
Abstract The objective of this work was to explore the impact of temperature on shale swelling and explain it in terms of diffuse double layer mechanics: Debye–Hückel length alterations. This was made possible through the use of a newly developed thermal linear swelling test. Moreover, the combined impact of temperature, dielectric constant of water and ionic strength (ionic concentration) of salt solutions on Debye–Hückel length and resultant shale swelling and shrinkage were investigated. For dilute solutions, results showed that the product of temperature and dielectric constant of water (T*εr) remained near constant for a wide range of temperature (25–90°C). Results suggest that the dielectric constant of water may have been reduced by both temperature and ionic strength of solution, all of which caused a greater reduction in Debye–Hückel length and subsequent shale shrinkage. As for saturated NaCl and CaCl2 solutions, shale exhibited swelling behaviour at moderate temperatures followed by shale shrinkage thereafter. This could be attributed to the development of repulsive forces between alike ions within diffuse double layer. At higher temperatures, the contribution of dielectric constant of water on lowering Debye–Hückel length may have softened the repulsion action produced by ions.